Trends in Pharmacologic Interventions for Preventing Recurrence of Crohn's Disease After Ileocolonic Surgery. Issue 10 (October 2016) - Ong, Mei-Sing; Grand, Richard J.; Mandl, Kenneth D.
Abstract : Background: Prophylactic treatment of postoperative Crohn's disease (CD) plays a critical role in maintaining clinical remission. We performed the first study in the last decade to examine secular trends in the use of pharmacologic interventions after ileocolonic resection in the United States, to understand whether clinical practice converges with recent advances in scientific knowledge. Methods: A retrospective study of a U.S. national claims database was performed. The study cohort included 106 CD patients in the years 1999 to 2001 (prebiologic era) and 294 CD patients in the years 2009 to 2011 (postbiologic era), who underwent ileocolonic resection. Medication use in the 12 months after the surgery was examined. Results: Significant variations in care were evident in both study periods. Across the 2 study periods, there was an increased use of biologics (from 0% to 36.4%) and a substantial reduction in the use of 5-aminosalicylic acid (from 50.9% to 28.2%; P < 0.0001). Therapeutic interventions that have been found ineffective in published studies continued to be widely applied: one-third of patients were prescribed corticosteroids, and several cases of prolonged use of corticosteroids or antibiotics were observed in both cohorts. Disease behavior (penetrating, stricturing, or nonpenetrating and nonstricturing) was not associated with the choice of postoperative therapeutic interventions, with the exception of an increased use of antibiotics among patients with penetrating disease. Conclusions: There is a substantial gap between advances in postoperative care for ileocolonic CD and clinical practice. Strategies to expedite the integration of new knowledge and evidence into practice are urgently needed. Abstract : Article first published online 22 August 2016.